Generation of electrostatics ion-cyclotron wave by parallel flow velocity shear in the presence of inhomogeneous electric field in an anisotropic magneto-plasma - Pandey R.S.; Misra K.D.; Tripathi A.K. (My University, 2025)
Generation of electrostatic ion-cyclotron wave and its harmonics, driven by parallel flow velocity shear in the presence of perpendicular inhomogeneous d.c. electric field and density gradient, is studied by using the characteristic method. The details of particle trajectories, dispersion relation and growth rate have been evaluated in the short wavelength region. The ion-cyclotron waves are excited at various harmonics of ion-cyclotron frequency. The growth rate is evaluated for ioncyclotron harmonic's for plasma parameters suited to magnetosphere. The dominant driving source of this instability is found to be the parallel flow velocity shear rather than the temperature anisotropy and temperature ratios of electron and ion. The electric field inhomogeneity has a destabilizing effect on ion-cyclotron instability.